Direct assessment of the metabolic origin of carbon atoms in glutamate from illuminated leaves using 13C‐NMR. Issue 4 (3rd August 2017) - Abadie, Cyril; Lothier, Jérémy; Boex‐Fontvieille, Edouard; Carroll, Adam; Tcherkez, Guillaume
Summary: Glutamate (Glu) is the cornerstone of nitrogen assimilation and photorespiration in illuminated leaves. Despite this crucial role, our knowledge of the flux to Glu de novo synthesis is rather limited. Here, we used isotopic labelling with 13 CO2 and 13 C‐NMR analyses to examine the labelling pattern and the appearance of multi‐labelled species of Glu molecules to trace the origin of C‐atoms found in Glu. We also compared this with 13 C‐labelling patterns in Ala and Asp, which reflect citrate (and thus Glu) precursors, that is, pyruvate and oxaloacetate. Glu appeared to be less 13 C‐labelled than Asp and Ala, showing that the Glu pool was mostly formed by 'old' carbon atoms. There were modest differences in intramolecular 13 C– 13 C couplings between Glu C‐2 and Asp C‐3, showing that oxaloacetate metabolism to Glu biosynthesis did not involve C‐atom redistribution by the Krebs cycle. The apparent carbon allocation increased with carbon net photosynthesis. However, when expressed relative to CO2 fixation, it was clearly higher at low CO2 while it did not change in 2% O2, as compared to standard conditions. We conclude that Glu production from current photosynthetic carbon represents a small flux that is controlled by the gaseous environment, typically upregulated at low CO2 .